2019
DOI: 10.1007/s40864-019-00114-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modelling for Decarbonisation in Urban Rail Systems

Abstract: This paper demonstrates a methodology for flexible, dynamic systems modelling relevant to urban rail decarbonisation. Decarbonisation of urban rail is a vital component of policy and strategy to minimize anthropogenic emissions. Decarbonisation is a systems problem, however, that needs to reflect the interaction between components and processes. Dynamic computer modelling of systems for decarbonisation involves interfacing multiple models together and running them in parallel in order to observe and predict sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Further details on the models are available in. 67 In order to enable DSE, two versions of the train model were developed; a standard model based on the Metro rolling stock current characteristics, and a power optimised version, which was light-weighted (from 40 metric tonnes to 35 metric tonnes) and with regenerative braking sub-model. The driver model was also developed in two variants -a baseline driver, and a 'defensive' driver -a driver who was slower in applying power and brake, as is typically exhibited in more energy efficient driving.…”
Section: Methodsmentioning
confidence: 99%
“…Further details on the models are available in. 67 In order to enable DSE, two versions of the train model were developed; a standard model based on the Metro rolling stock current characteristics, and a power optimised version, which was light-weighted (from 40 metric tonnes to 35 metric tonnes) and with regenerative braking sub-model. The driver model was also developed in two variants -a baseline driver, and a 'defensive' driver -a driver who was slower in applying power and brake, as is typically exhibited in more energy efficient driving.…”
Section: Methodsmentioning
confidence: 99%
“…This was developed as a high-fidelity model where each submodel was created independently and can be easily swapped for another of the same type, similar to functional mock-up units (FMUs). [29][30][31] The components are discussed in more detail below. This is based upon the Hitachi AT300 product family (Class 800, 801 and 802, here denoted as 80x) of trains currently being introduced onto the UK rail network.…”
Section: Vehicle Energy Consumption Reductionmentioning
confidence: 99%
“…They showed that in order to achieve 1.5 • C temperature stabilization, direct actions and transformations in technology and human behaviour are essential. Golightly et al [14] developed a multi-modelling approach for urban rail decarbonization but did not include other transport segments. Küng et al [15] analyzed CO 2 reduction potential of different vehicle fleet compositions, considering different CO 2 intensities of the electricity mix.…”
Section: State Of the Artmentioning
confidence: 99%